2018
DOI: 10.1111/ajag.12524
|View full text |Cite
|
Sign up to set email alerts
|

‘An ant against an elephant’: Retirement village residents’ experiences of disputes and dispute resolution

Abstract: Despite finding retirement village life positive, residents of retirement villages found disputes and dispute resolution processes unsatisfactory and desired change to address these concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…Retirement villages often have a residents committee to have some control and be in more direct contact with the management (Croucher et al , 2003; Croucher and Bevan, 2010). Informational flows between management and residents can be an issue of critique, with residents not knowing about processes (Malta et al , 2018), but newsletters are seen as an effective way to keep people informed about a range of issues, also to counteract rumours (Croucher and Bevan, 2010). Retirement villages also have been shown to have sanctioning capabilities as facilities’ rules, such as dress codes for dinners, are enforced in some of them (Shippee, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Retirement villages often have a residents committee to have some control and be in more direct contact with the management (Croucher et al , 2003; Croucher and Bevan, 2010). Informational flows between management and residents can be an issue of critique, with residents not knowing about processes (Malta et al , 2018), but newsletters are seen as an effective way to keep people informed about a range of issues, also to counteract rumours (Croucher and Bevan, 2010). Retirement villages also have been shown to have sanctioning capabilities as facilities’ rules, such as dress codes for dinners, are enforced in some of them (Shippee, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst there are reported health benefits to retirement village living, contractual arrangements and dispute resolution can raise challenges. An independent survey conducted by Malta and colleagues in Victoria confirmed that the majority of residents were satisfied with their living arrangements and experiences of dispute resolution. However, 38% of issues remained unresolved/were unsatisfactorily resolved.…”
Section: Congregate Housing Optionsmentioning
confidence: 96%
“…Further, it is important to recognize that their needs transition over time, and hence their satisfaction with services also changes 16 . For example, the later years of life bring unique challenges for which may lead them to seek out new services and service experiences 17,18 . Therefore, in order to develop services that meet their changing needs, it is imperative that service providers continue to develop an in‐depth understanding of older peoples' needs, and the components of their satisfaction.…”
Section: Introductionmentioning
confidence: 99%